Low-temperature thermal transport and thermopower of monolayer transition metal dichalcogenide semiconductors. (1st September 2017) - Sengupta, Parijat; Tan, Yaohua; Klimeck, Gerhard; Shi, Junxia
Abstract: We study the low temperature thermal conductivity of single-layer transition metal dichalcogenides (TMDCs). In the low temperature regime where heat is carried primarily through transport of electrons, thermal conductivity is linked to electrical conductivity through the Wiedemann–Franz law (WFL). Using a k.p Hamiltonian that describes the K and K ′ valley edges, we compute the zero-frequency electric (Drude) conductivity using the Kubo formula to obtain a numerical estimate for the thermal conductivity. The impurity scattering determined transit time of electrons which enters the Drude expression is evaluated within the self-consistent Born approximation. The analytic expressions derived show that low temperature thermal conductivity (1) is determined by the band gap at the valley edges in monolayer TMDCs and (2) in presence of disorder which can give rise to the variable range hopping regime, there is a distinct reduction. Additionally, we compute the Mott thermopower and demonstrate that under a high frequency light beam, a valley-resolved thermopower can be obtained. A closing summary reviews the implications of results followed by a brief discussion on applicability of the WFL and its breakdown in context of the presented calculations.